2018
DOI: 10.1007/s10548-018-0643-x
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness Indexing and Outcome Prediction with Resting-State EEG in Severe Disorders of Consciousness

Abstract: We applied the following methods to resting-state EEG data from patients with disorders of consciousness (DOC) for consciousness indexing and outcome prediction: microstates, entropy (i.e. approximate, permutation), power in alpha and delta frequency bands, and connectivity (i.e. weighted symbolic mutual information, symbolic transfer entropy, complex network analysis). Patients with unresponsive wakefulness syndrome (UWS) and patients in a minimally conscious state (MCS) were classified into these two categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 48 publications
6
113
0
Order By: Relevance
“…Thus, a higher value of entropy indicates that the subject is awake, while lower values indicate deeper unconsciousness (Bruhn et al, 2003;Gosseries et al, 2011;Wu et al, 2011;Thul et al, 2016). It has been found that the mean values of approximate entropy (ApEn) were significantly lower in patients than controls (Sarà and Pistoia, 2010;Sarà et al, 2011;Wu et al, 2011;Stefan et al, 2018) and also the mean EEG entropy values for DOC patients had a positive linear correlation with CRS-R scores (Bruhn et al, 2003). Further, Lempel-Ziv complexity (LZC) and cross-approximate entropy values were significantly lower for the PVS, followed by MCS, and the highest for controls (Wu et al, 2011).…”
Section: Studies Based On Resting-state Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a higher value of entropy indicates that the subject is awake, while lower values indicate deeper unconsciousness (Bruhn et al, 2003;Gosseries et al, 2011;Wu et al, 2011;Thul et al, 2016). It has been found that the mean values of approximate entropy (ApEn) were significantly lower in patients than controls (Sarà and Pistoia, 2010;Sarà et al, 2011;Wu et al, 2011;Stefan et al, 2018) and also the mean EEG entropy values for DOC patients had a positive linear correlation with CRS-R scores (Bruhn et al, 2003). Further, Lempel-Ziv complexity (LZC) and cross-approximate entropy values were significantly lower for the PVS, followed by MCS, and the highest for controls (Wu et al, 2011).…”
Section: Studies Based On Resting-state Analysismentioning
confidence: 99%
“…Non-linear analysis of resting EEG using indices like complexity and entropy has also been used in several studies (Sarà and Pistoia, 2010;Gosseries et al, 2011;Sarà et al, 2011;Wu et al, 2011;Sitt et al, 2014;Stefan et al, 2018;Zhu et al, 2019) to quantify the degree of consciousness in DOC patients. Entropy of EEG is a measure of its regularity.…”
Section: Studies Based On Resting-state Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, GBI processes suggest that the role of inhibition is more complex than preventing excessive activation of brain networks, contributing instead to shaping anatomical brain networks into functional networks (Avena-Koenigsberger et al, 2017). Possible alterations of GBI were reported in studies showing that EEG alpha power is lower in UWS than in MCS patients (Lehembre et al, 2012;Stefan et al, 2018), hinting that the neurobiological mechanisms underlying alpha oscillations generation and associated GBI are profoundly altered in unresponsive patients. Moreover, alpha activity was highly synchronized and clustered in central and posterior cortical regions in UWS patients (Lehembre et al, 2012;Stefan et al, 2018), suggesting a possible failure of GBI in the most severe disorders of consciousness.…”
Section: Functional Network a Flexible Architecture For Conscious Pmentioning
confidence: 99%
“…This is a more advanced step in the differential diagnosis, as it requires denser EEG recording electrodes (e.g., [63,64,73,74]) and specific analytic and statistical procedures. In particular, EEG-based connectivity assessment is useful to differentiate and prognosticate patients with DoC, especially using active tasks [79].…”
Section: Electroencephalogram Assessmentmentioning
confidence: 99%